A PC-based controller for the computer numerically-controlled (CNC) laser machine - Rogelio, Jayson P. (Animo Repository, 2015)
This study presents the development of a PC-based controller for the 3-axis computer numerically-controlled (CNC) LASER machine. This includes the use of an MK-II motion controller board in controlling the three (3) Ezi-Servo stepper motors and in enabling the LASER output from the Synrad firestar f201. The LASER power output is controlled using a developed PWM controller. The machine was tested both in functional and performance testing. In terms of performance, it can cut mild steel and stainless steel with thickness of 2 mm and 1 mm, respectively. PLT extension file was used for the g-code toolpath of the CNC LASER machine system.